Antibodies to extractable nuclear antigens (ENAS) in systemic lupus erythematosus patients: correlations with clinical manifestations and disease activity - Y. Emad; T. Gheita; H. Darweesh; P. Klooster; R. Gamal; H. Fathi; N. El-Shaarawy; M. Gamil; M. Hawass; R.M. El-Refai; H. Al-Hanafi; S. Abd-Ellatif; et al. (PAGEPress Publications, 2018)
The aim was to explore possible correlations of antibodies to extractable nuclear antigens (ENA) with clinical manifestations and disease activity indices in systemic lupus erythematosus (SLE) patients. A total of 70 consecutive SLE patients (64 females) were included. Disease activity was assessed by SLE activity index (SLEDAI), and British Isles Lupus Assessment Group (BILAG). Anti-Ro/SSA correlated positively with, headache (r=0.24, p=0.04), blurring of vision (r=0.25, p=0.03) and SLEDAI (r=0.25, p=0.04) and negatively with C3 (r=-0.35, p=0.003). Anti-Ro/SSA correlated with anti La/SSB antibodies (r=0.69, p<0.001), but not with anti-DNA, anti-RNP and anti-Sm antibodies. Anti-La/SSB antibodies correlated with headache (r=0.26, p=0.03), SLEDAI (r=0.25, p=0.03) and negatively with C3 (r=-0.34, p=0.004). Anti-La/SSB did not correlate with anti-RNP or anti-Sm antibodies. Anti-Sm antibodies correlated with disease duration (r=0.34, p=0.003), 24 hours urinary proteins (r=0.31, p=0.008), SLEDAI (r=0.31, p=0.009), BILAG renal score (r=0.29, p=0.02) and negatively with age at onset (r=-0.27, p=0.02), WBCs (r=-0.29, p=0.014) and C4 (r=-0.25, p=0.049). In multivariate analyses, anti-Ro/SSA antibodies remained associated with headache, blurring of vision and C3 and anti-La/SSB antibodies remained associated with C3 and with headache. Anti-Sm antibodies were independently associated with disease duration and total SLEDAI scores, while anti-RNP antibodies remained significantly associated with BILAG mucocutaneous scores only. Antibodies to ENAs are associated with clinical aspects of SLE and may play a role in the assessment of disease activity. Insight into these ENAs may lead to new approaches to diagnostic testing, accurate evaluation of disease activity and lead to target approach for SLE.